ANALISIS HUBUNGAN TINGKAT PENDAPATAN DENGAN KEPUTUSAN KONSUMEN DALAM MEMBELI MINYAK GORENG - Adinda Harahap; Gilang Ramadhan; Siti Rahma; Tasya Azzahra; Siti Suaibah Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to evaluate the relationship between income levels and consumer decisions in buying cooking oil. Data was obtained by sampling using the “proportional random sampling” technique with a sample of 40 respondents with a questionnaire as a data collection tool that had been prepared previously. The analysis method used is the Chi-Square test to test the significance of the relationship between income variables and purchasing preferences. Data processing was assisted by statistical package social science (SPSS) version 30. This research was conducted in May 2025. The research findings show that income has a significant effect on consumer decisions on the selection of cooking oil in the traditional market Simpang Limun Medan.